Towards a linguistic theory of translation as re-contextualisation and a Third Space phenomenon - House, Juliane (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The article suggests a theory of translation as re-contextualisation and a ‘Third Space’ phenomenon supplementing the ideas recently suggested in the cultural branch of translation studies with a linguistic account and building a bridge between the two. The view proposed here is rooted in a functional approach to translation. Such an approach is fruitful because it implies a systematic consideration of the context of translation units and the embeddedness of language as a meaning-making tool in micro-situational and macro-sociocultural contexts. The categorically different nature of Third Space in covert and overt translation is exemplified and explained with reference to House ’s theory of translation as re-contextualisation. Finally, possible changes in conceptualizing translation as a Third Space phenomenon are mentioned with a view to the growing dominance of English as a global lingua franca.